The effect of mate tea (Ilex paraguariensis) on metabolic and inflammatory parameters in high-fat diet-fed Wistar rats. (August 2013) - Borges, Maria Carolina; Vinolo, Marco Aurélio Ramirez; Nakajima, Karina; de Castro, Inar Alves; Bastos, Deborah Helena Markowicz; Borelli, Primavera; Fock, Ricardo Ambrósio; Tirapegui, Julio; Curi, Rui; Rogero, Marcelo Macedo
<x xml:space="preserve">Abstract</x> This study investigated the effects of mate tea (Ilex paraguariensis) aqueous extract consumption on metabolic indicators and inflammatory response of peritoneal macrophages in rats fed a high-fat diet (HFD). Male Wistar rats were fed a control diet or a HFD for 12 weeks. At the end of this period, rats received, or not, daily doses of yerba maté for 4 weeks. The consumption of yerba maté promoted weight loss, attenuated the HFD-detrimental effects on adiposity and insulin sensitivity and decreased blood levels of the inflammatory biomarkers (p < 0.05). Concerning peritoneal macrophages, mate tea consumption decreased the production of interleukin (IL)-6, but did not influence the production of IL-1β, tumour necrosis factor-α and nitric oxide; cytokine mRNA expression; or the activation of the nuclear factor-κB signalling pathway. In summary, the consumption of mate tea had no consistent effect in the inflammatory response of peritoneal macrophages, but reduced cardiometabolic risk markers.